Oxygen uptake kinetics during treadmill walking in adolescents with clinically stable cystic fibrosis. (3rd October 2022) - Combret, Yann; Medrinal, Clément; Prieur, Guillaume; Robledo Quesada, Aurora; Gillot, Timothée; Gravier, Francis-Edouard; Bonnevie, Tristan; Lamia, Bouchra; Le Roux, Pascal; Reychler, Grégory
ABSTRACT: Background: Oxygen uptake (V̇O2 ) kinetics have been shown to be slowed in adolescents with cystic fibrosis (CF) during heavy-intensity cycling and maximal exercise testing. Objectives: This study investigated V̇O2 kinetics in adolescents with CF compared to control adolescents (CON) during a treadmill-walking exercise. Methods: Eight adolescents with CF and mild-to-moderate pulmonary obstruction (5 girls; 13.1 ± 2.5 years; FEV1 67.8 ± 21.4%) and 18 CON adolescents (10 girls; 13.8 ± 1.8 years) were recruited. Pulmonary gas exchange and ventilation were measured during a single transition of 10 min of treadmill walking and a 5 min seated recovery period. Participant's walking speed was determined during a one-minute self-paced walking task along a 50-m corridor. A six-parameter, non-linear regression model was used to describe the changes in V̇O2 function during the treadmill walking and recovery, with monoexponential curve fitting used to describe the mean response time (MRT1 ) at the onset of exercise, and the half-life (T1/2 V̇O2 ) at the offset of exercise. V̇O2 baseline and amplitude, minute ventilation and respiratory equivalents were recorded. Results: V̇O2 kinetics were slower in CF group compared to CON group during the treadmill walking with a greater MRT1 (32 ± 14 s vs 21 ± 16 s; p = .04, effect size = 0.75). The T1/2 V̇O2 was prolonged during recovery in CF group compared to CON group (86 ± 24 s vs 56 ± 22 s; p = .04, effect size = 1.31). The mean VE/V̇CO2 during exercise was the only parameter significantly greater in CF group compared to CON group (32.9 ± 2.3 vs 29.0 ± 2.4; p < .01, effect size = 1.66). Conclusion: V̇O2 kinetics were found to be slowed in adolescents with CF during treadmill walking.